Adubação nitrogenada associada a inoculação com Azospirillum brasilense na cultura do milho - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Corn (Zea mays) is a world-class crop due to its diversity of use, the extension of cultivated area and its high production capacity. One of the alternatives to decrease the nitrogen fertilizer consumption in the crop is the use of seed inoculation with diazotrophic bacteria that has the capacity to fix the atmospheric N in the soil. The objective of this work was to verify the effect of the use of bacteria of the genus Azospirillum brasilense inoculated via seeds in a gradual association with nitrogen doses in the grain yield and other agronomic characteristics in the maize crop. The experiment was conducted in the field from November 24, 2016 to March 29, 2017, in the experimental area of the Federal University of Pampa - UNIPAMPA, Campus Itaqui (RS). The treatments were arranged in randomized blocks with four replicates. The inoculation of corn seeds with Azospirillum brasilense (presence or absence) and doses of N in cover (0, 25, 50, 75, 100% of N) were tested in two applications. The following were evaluated: plant height, ear insertion height, spike weight, one thousand grain mass and grain yield. The inoculation of corn seeds with Azospirillum brasilense does not increase the yield of grains and does not alter the height of plants, height of the insertion of the spike mass of a thousand grains. The application of N on cover in maize positively influences grain yield.
Keywords: Zea mays; Bactérias diazotróficas; Nitrogênio; Rendimento de grãos; Diazotrophic bacteria; Nitrogen; Yield of grains; CNPQ::CIENCIAS AGRARIAS